The Laboratory of the Revolution : Tabasco under Tomás Garrido Canabál, 1922-1935 - Martínez Assad, Carlos, (Critical Latin America ;, 2026)
Laboratory of the Revolution is the first-ever professional study of Tomás Garrido Canabal, revolutionary strongman of Tabasco state between 1922 and 1935. He dreamed of turning Tabasco-an isolated backwater and the quintessential "banana republic"-into a beacon of progress. Garrido's recipe for that progress consisted of ridding the state of religion, prohibiting alcohol and other vices, championing science, and boosting agriculture and ranching. He only fell from power when a shoot-out in Tabasco furnished the pretext for subordinating the state to President Lázaro Cárdenas's centrally governed political machine, the forerunner of Mexico's long-lived one-party system.